Criminal Measures to Combat Administrative Corruption in Iraq - Jabbar Ashour, Ameel (Opción, 2019)
The aim of this study is to contribute to the reduction of administrative and financial corruption crimes that are rampant in Iraqi government institutions and departments. This study is based on a qualitative approach by analyzing primary and secondary sources. In result, the study found that the reasons for the spread of administrative and financial corruption in Iraqi institutions are due to the weak legal and procedural mechanisms. In conclusion, there is no precise definition for the crime of corruption and it is due to the overlap of issues and the different visions of the different countries’ legislatures.